2016
DOI: 10.1136/bmj.i2200
|View full text |Cite
|
Sign up to set email alerts
|

Management of diabetes mellitus in older people with comorbidities

Abstract: Diabetes mellitus is a chronic disease of aging that affects more than 20% of people over 65. In older patients with diabetes, comorbidities are highly prevalent and their presence may alter the relative importance, effectiveness, and safety of treatments for diabetes. Randomized controlled trials have shown that intensive glucose control produces microvascular and cardiovascular benefits but typically after extended treatment periods (five to nine years) and with exposure to short term risks such as mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
59
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 72 publications
4
59
3
1
Order By: Relevance
“…The complexity of caring for patients with diabetesmultimorbidity has been previously recognized 6,7 and attributed to several reasons. First, specific diabetes-multimorbidity combinations may affect patients' ability to perform selfmanagement activities, resulting in suboptimal diabetes control.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of caring for patients with diabetesmultimorbidity has been previously recognized 6,7 and attributed to several reasons. First, specific diabetes-multimorbidity combinations may affect patients' ability to perform selfmanagement activities, resulting in suboptimal diabetes control.…”
Section: Introductionmentioning
confidence: 99%
“…The presenting findings in which majority of the patients sampled were between the ages of 51 and above are similar to those of earlier reports by Selvin et al (16), who reported prevalence of diabetes to be among the elderly individuals. Other studies have also reported that diabetes and its complications increase with increasing age (17,18). Thus, age is a major risk factor for diseases inclusive of diabetes mellitus, and this factor can be affected by educational levels of the patients.…”
Section: Discussionmentioning
confidence: 95%
“…1–3 Selecting the optimal treatment regimen for older adults with type 2 diabetes requires special considerations. 46 Older adults with diabetes often have multiple comorbid conditions that may present medication contraindications or interactions that limit the use of certain pharmacologic classes. 48 Functional and cognitive limitations become more common with aging which could limit the use of complex regimens.…”
mentioning
confidence: 99%
“…48 Functional and cognitive limitations become more common with aging which could limit the use of complex regimens. 46,9 Further, preventing hypoglycemia is critical for older patients, and guidelines recommend avoiding medications with the highest hypoglycemia risk, particularly long-acting sulfonylureas and sliding-scale insulin. 46,1012 …”
mentioning
confidence: 99%
See 1 more Smart Citation